Influence of Combination Antiretroviral Therapy on HIV-1 Serological Responses and Their Implications: A Systematic Review and Meta-Analysis - Liang, Yuanhao; Lin, Hongqing; Dzakah, Emmanuel Enoch; Tang, Shixing (Frontiers in Immunology, 2022)
We aimed to analyze HIV-1 seroreversion caused by combination antiretroviral therapy (cART) and to explore antibody levels of anti-HIV-1 as an alternative biomarker of HIV-1 reservoir. We searched PubMed, Embase, the Cochrane Library, and Web of Science up to August 2021 for publications about the performance of HIV-1 serological assays or the association between antibody responses against HIV-1 and HIV-1 reservoirs. Potential sources of heterogeneity were explored by meta-regression analysis, including the year of publication, country, pretreatment viral load, sample size, the timing of treatment, time on cART, and principle or type of serological assay. Twenty-eight eligible studies with a total population of 1,883 were included in the meta-analysis. The pooled frequency of HIV-1 seronegativity is 38.0% (95% CI: 28.0%–49.0%) among children with vertical HIV-1 infection and cART initiation at the age of less than 6 months, while the percentage of HIV-1 seronegativity declined to 1.0% (95% CI: 0%–3.0%) when cART was initiated at the age of >6 months. For adult patients, 16.0% (95% CI: 9.0%–24.0%) of them were serologically negative when cART was initiated at acute/early infection of HIV-1, but the seronegative reaction was rarely detected when cART was started at chronic HIV-1 infection. Substantial heterogeneity was observed among the studies to estimate the frequency of HIV-1 seronegativity in the early-cART population (I2 ≥ 70%, p < 0.05 and all), while mild heterogeneity existed for the deferred-cART subjects. Moreover, anti-HIV-1 antibody response positively correlates with HIV-1 reservoir size with a pooled rho of 0.43 (95% CI: 0.28–0.55), suggesting that anti-HIV antibody level may be a feasible biomarker of HIV-1 reservoir size.